Evaluation of the application PermenKUKM No. 13 in cooperative savings and loan accounting Bali State Polytechnic Cooperative - Sugiarta, I Komang; Ardina, Cening; Parnata, I Ketut (Proceedings; 2020: The 2nd International Conference on Applied Science and Technology (iCAST) 2019 Proceeding, 2020)
The ministry of cooperatives and small medium enterprises has issued Permen No. 13/Per/M.KUKM/IX/2015 concerning accounting guidelines for savings and loan business by cooperatives which must be used as a guide in preparing and presenting the financial statements of this business unit. With the issuance of the ministerial regulation, it is expected that cooperatives can increase accountability in the preparation of their financial statements. But the fact is that there are cooperatives that have not prepared and presented financial reports in accordance with the guidelines. This study was aimed at evaluating its application in the savings and loan unit of Bali State Polytechnic cooperative. Based on the results of research conducted, it was found that there were three reports that were not presented in the financial statements of the savings and loans unit, namely: statement of changes in equity, cash flow, and notes to financial statements. In addition, in presenting the financial position report, found several accounts that are not in accordance with the guidelines, namely: banks, bank loans, education funds, social funds, and development funds. Likewise, in the presentation of the remaining results business report, there were no cooperative expense accounts, such as: costs for education and training for cooperative hr, organizational meeting fees, and fees for supervisors. The findings of this study are expected to be used as recommendations to the management of the Bali State Polytechnic Cooperative in preparing and presenting the financial statements of the Savings and Loan Unit in the next period.